The evaluation of serological tests in the diagnosis of bovine brucellosis in naturally infected cattle in Kwazulu-Natal Province, South Africa - Van Heerden, Henriette (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2013.